The future of cow’s milk allergy – milk ladders in IgE-mediated food allergy - Hicks, Allison; Fleischer, David; Venter, Carina (Frontiers in Nutrition, 2024)
Cow’s milk allergy (CMA) is one of the most common and complex presentations of allergy in early childhood. CMA can present as IgE and non-IgE mediated forms of food allergy. Non-IgE mediated CMA includes food protein-induced enterocolitis syndrome (FPIES), eosinophilic gastrointestinal disorders (EGIDs), and food protein-induced proctocolitis (FPIAP). There are recent guidelines addressing CMA diagnosis, management, and treatment. Each of these guidelines have their own strengths and limitations. To best manage CMA, individualized avoidance advice should be given. Cow’s milk (CM) can be replaced in the diet by using hypoallergenic formulas or plant-based milk, depending on factors such as the child’s age and their current food intake. Oral and epicutaneous immunotherapy is used to increase tolerance in children with CMA but is not without risk, and the long-term outcome of sustained unresponsiveness is still unclear. The allergenicity of CM proteins are affected differently by different forms of heating, leading to the use of baked milk or milk ladders in the management of CMA, most likely the most promising option for future management and treatment of CMA. Future management of children with CMA will also include discussion around the immunomodulatory potential of the child’s dietary intake.